A new species of the genus Scincella (Squamata: Scincidae) from Yonagunijima Island, Southern Ryukyus, Japan - Koizumi, Yuki; Ota, Hidetoshi; Hikida, Tsutomu (Zootaxa, 2022)
We performed a molecular phylogenetic analysis for the ground skink populations of the genus Scincella Mittleman, 1950 on Yonagunijima Island, Southern Ryukyus and representative samples of Scincella species known from other islands of the East Asian Archipelago. Partial mitochondrial cytochrome c oxidase subunit I and cytochrome b sequence data were used. Additionally, we examined the nuclear genetic variation between the Yonagunijima samples and those of closely related species. The genetic distances were largely equivalent between the Yonagunijima population and the two closest species, S. boettgeri from other southern Ryukyu Islands and S. formosensis from Taiwan. Moreover, there were nuclear haplotypes unique to the Yonagunijima population. We thus recognize the Yonagunijima population as a distinct species and describe it as Scincella dunan sp. nov. Morphologically, S. dunan sp. nov. is similar to S. boettgeri, but differs in some morphometric and meristic characters, and dorsolateral stripe pattern. These findings further support the biogeographically unique status of Yonagunijima Island among the southern Ryukyus islands.